Vulnerability and Relationship Satisfaction: Mediation of Smartphone Addiction - Satici, Begum (IGI GLOBAL, 2022)
The present study aimed to investigate the mediating role of smartphone addiction in the association between vulnerability and relationship satisfaction among younger adults living in Turkey. The relationship assessment scale, the smartphone addiction scale-short version, the psychological vulnerability scale, and the social vulnerability scale were applied to 326 university students. Structural equation modelling showed that vulnerability has a significantly direct effect on relationship satisfaction, and smartphone addiction can partially mediate the impact of vulnerability on relationship satisfaction. The bootstrapping techniques confirmed that smartphone addiction had a partial mediation effect between vulnerability and relationship satisfaction. These data may help clinicians and researchers to better understand the consequences of vulnerability and underlying the processes of smartphone addiction and relationship satisfaction.
Keywords: Relationship Satisfaction; Smartphone Addiction; Structural Equation Modeling; Vulnerability; PSYCHOLOGICAL VULNERABILITY; ASSOCIATIONS; RISK; PERSONALITY; DEPRESSION; TRAITS; USAGE; MODEL; LIFE; Information Science & Library Science